Pomalidomide plus low-dose dexamethasone versus high-dose dexamethasone alone for patients with relapsed and refractory multiple myeloma (MM-003): a randomised, open-label, phase 3 trial - San-Miguel, Jesús F.; Weisel, Katja; Moreau, Philippe; Lacy, Martha; Song, Kevin; Delforge, Michel; Karlin, Lionel; Goldschmidt, Hartmut; Banos, Anne; Oriol, Albert; Alegre, Adrian; Chen, Christine; et al. (The lancet. Oncology, 2013)
Background - Few effective treatments exist for patients with refractory or relapsed and refractory multiple myeloma not responding to treatment with bortezomib and lenalidomide. Pomalidomide alone has shown limited efficacy in patients with relapsed multiple myeloma, but synergistic effects have been noted when combined with dexamethasone. We compared the efficacy and safety of pomalidomide plus low-dose dexamethasone with high-dose dexamethasone alone in these patients. - Methods - This multicentre, open-label, randomised phase 3 trial was undertaken in Australia, Canada, Europe, Russia, and the USA. Patients were eligible if they had been diagnosed with refractory or relapsed and refractory multiple myeloma, and had failed at least two previous treatments of bortezomib and lenalidomide. They were assigned in a 2:1 ratio with a validated interactive voice and internet response system to either 28 day cycles of pomalidomide (4 mg/day on days 1-21, orally) plus low-dose dexamethasone (40 mg/day on days 1, 8, 15, and 22, orally) or high-dose dexamethasone (40 mg/day on days 1-4, 9-12, and 17-20, orally) until disease progression or unacceptable toxicity. Stratification factors were age (≤75 years vs >75 years), disease population (refractory vs relapsed and refractory vs bortezomib intolerant), and number of previous treatments (two vs more than two). The primary endpoint was progression-free survival (PFS). Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT01311687, and with EudraCT, number 2010-019820-30. - Findings - The accrual for the study has been completed and the analyses are presented. 302 patients were randomly assigned to receive pomalidomide plus low-dose dexamethasone and 153 high-dose dexamethasone. After a median follow-up of 10·0 months (IQR 7·2-13·2), median PFS with pomalidomide plus low-dose dexamethasone was 4·0 months (95% CI 3·6-4·7) versus 1·9 months (1·9-2·2) with high-dose dexamethasone (hazard ratio 0·48 [95% CI 0·39-0·60]; p<0·0001). The most common grade 3-4 haematological adverse events in the pomalidomide plus low-dose dexamethasone and high-dose dexamethasone groups were neutropenia (143 [48%] of 300 vs 24 [16%] of 150, respectively), anaemia (99 [33%] vs 55 [37%], respectively), and thrombocytopenia (67 [22%] vs 39 [26%], respectively). Grade 3-4 non-haematological adverse events in the pomalidomide plus low-dose dexamethasone and high-dose dexamethasone groups included pneumonia (38 [13%] vs 12 [8%], respectively), bone pain (21 [7%] vs seven [5%], respectively), and fatigue (16 [5%] vs nine [6%], respectively). There were 11 (4%) treatment-related adverse events leading to death in the pomalidomide plus low-dose dexamethasone group and seven (5%) in the high-dose dexamethasone group. - Interpretation - Pomalidomide plus low-dose dexamethasone, an oral regimen, could be considered a new treatment option in patients with refractory or relapsed and refractory multiple myeloma. - Funding - Celgene Corporation.
Gesehen am 27.01.2022